Faktor Gangguan Ginjal dan Diabetes Melitus yang Mempengaruhi Mortalitas Penderita Sindrom Koroner Akut di RSUD Dr. H. Abdul Moeloek Tahun 2020–2021 - Fadhlurrahman, Fadhlurrahman; Yonata, Ade; Karima, Nisa; Kurniati, Intanri (Medula, 2025)
Acute Coronary Syndrome (ACS) is one of the leading causes of cardiovascular mortality worldwide and in Indonesia. Various risk factors have been investigated, yet two important comorbidities that frequently worsen the prognosis are diabetes mellitus and kidney disorders. Diabetes mellitus accelerates atherosclerosis and promotes plaque instability, whereas kidney disorders exacerbate cardiovascular metabolism and restrict therapeutic options due to impaired drug elimination. This study aimed to analyze the influence of diabetes mellitus and kidney disorders on the mortality of ACS patients at Dr. H. Abdul Moeloek General Hospital. An analytic observational study with a cross-sectional design was conducted involving 71 patients diagnosed with ACS during the 2020–2021 period. The main independent variables were diabetes mellitus and kidney disorders, while mortality served as the dependent variable. Data were analyzed using the Chi-Square test, Fisher’s Exact Test, and Odds Ratio (OR) calculations, with a significance level of p < 0.05. The study found an overall mortality rate of 25.3% among ACS patients. A significant relationship was observed between diabetes mellitus and mortality (p = 0.012; OR = 3.1) as well as between kidney disorders and mortality (p = 0.019; OR = 4.0). This indicates that ACS patients with diabetes mellitus have approximately three times higher risk of death, and those with kidney disorders have about four times higher risk compared to those without these comorbidities. In conclusion, diabetes mellitus and kidney disorders are significant predictors of mortality among ACS patients, highlighting the importance of comprehensive management for patients with these conditions in clinical cardiovascular care.